Ties that bind : attachment formation in the maltreated preadolescent child placed in long term foster care - Chinnery, Shirley-Ann (Massey University, 1999)
While the Children, Young Persons, and Their Families Act 1989 enshrines the primacy of family placement for children in need of care and protection, it simultaneously acknowledges by way of S.13 (h) that for some children this may not be a viable, available or safe option and where such circumstances prevail, children are to be given the opportunity to develop an alternate psychological tie to caregivers other than their primary kin. lt is this small group of children who require long term alternate care that are of primary interest to this thesis. The legislative principle that mandates this practice is founded, in large part, on attachment theoretic assumptions. This conceptual framework also informs the current study. This research aims to investigate, by way of the case study method, the attachment experiences of a small sample of previously maltreated, New Zealand European preadolescent children in long term state care. The effects their attachment experiences have on the formation of a new attachment relationship with alternate caregivers and the facilitative or impeding role played by social workers and their organisation (NZCYPFA) in regard to the development of this relationship are examined. The field work involved a multimodal exploration of the above relationships and included four sets of participants: a key informant group, three social workers, five caregivers and three preadolescent children. Fundamental to this research is the need to identify factors integral to performing a social work assessment of attachment of both prospective caregivers and the preadolescent child requiring placement. Foster care literature, drawing on attachment theoretic constructs, would suggest that this process is imperative to making sound placement decisions and for ensuring placement stability (Thoburn, 1997; McAuley, 1996; Triseliotis, Sellick & Short, 1995). Attachment theory indicates that placement stability is linked to caregiver sensitivity and the development of relational mutuality (Brethefton, 1996; 1993; 1987; Howes & Segal, 1993; Marcus, 1991). These variables have also been associated with relational continuity which in turn has been implicated in positive developmental outcomes for children (Lyons-Ruth, 1996; Cicchetti, Toth & Lynch, 1995; Bowlby, 1988; 1982; 1980; 1973). This thesis documents similar findings, and concludes with a set of recommendations for social work policy, practice and future research.
Keywords: Foster care; Foster children; Attachment behaviour